THE DEPENDENCE OF ON- AND OFF-STATE GENERATIONS IN CLASSICAL MICROQUASARS FROM THE DISK DENSITY. 3-D NUMERICAL HYDRODYNAMICAL SIMULATIONS OF THE HIGH AND LOW MASS ACCRETION RATE IN ACCRETION DISK IN MICROQUASAR CYG X-1 - Nazarenko, V. (Одеські астрономічні публікації, 2018)
In the present work we have computed and have compared the on- and oﬀ- generations in low and high mass accretion rate accretion disks. The comparison shows that in the case of low mass accretion rate in disk (10−10 solar mass per year) the ON-state time interval is very short, order of 0.2 ч 0.4 of precession period; in the case of high mass accretion rate in disk (10−9 solar mass per year) the ON-state time interval is relatively long, order of 0.7 ч 0.9 of precession period. This shows that in the case more dense disk ON-states are relatively very long time interval because of high mass accretion rate in disk. This result is natural for classical microquasar (CYG X-1) in which the on-states are corresponding high mass accretion rates. For comparison we may also write that the time intervals of OFF-states in the present calculations are order of 1.3 ч 1.5 of precession periods. The calculations also show that in OFF-states the accretion disk have the low speciﬁc viscosity and on contrary have the high speciﬁc angular momentum. In ON-states the disk have to contrary to OFF-states the high speciﬁc viscosity and low speciﬁc angular momentum. It shows that in OFF-states the disk is very rapidly rotating with low viscosity. In ON-states the situation is on contrary. Such the disk time-behaviour is true for both low and high mass accretion rate. The calculations also show that in ON-states the disk radius is very small, order of 0.08 of the orbital separations and on contrary in OFF-states the disk radius is relatively large, order of 0.25 of the orbital separations. The stated above shows that the disk is strong transformed from ON- to OFF-states.